Análise de parâmetros acústicos e psicoacústicos da sonoridade do oboé associados aos diferentes estilos de raspados de palheta - Ravi Shankar Viana Domingues (2018)
The present thesis deals with the analysis of acoustic and psychoacoustic parameters related to the two main models of oboe reeds: short scraping and long scraping. The materials and procedures used in the production of the oboe reeds and several aesthetic concepts allied to the typology of scraping are presented in the introduction, as well as the historical development of the oboe and its reed, the scrapes mostly used in Brazil and the importance of the reed in the musical performance of the oboist. A descriptive cross -sectional study was carried out between September and December 2017 in the states of Paraíba and Rio Grande do Norte. Data collection was performed in two stages: recording two contrasting excerpts performed by 21 Brazilian and foreign professional oboists, whose data were collected through a semi-structured questionnaire, and the application of a subjective aural test to 73 musicians, faculties and students of of three universities. The recordings were analyzed according to acoustic descriptors and subsequent statistical treatment. The acoustic data, extracted through the descriptors, were contrasted with the data collected in the questionnaire and in the subjective aural test. It can be observed that the physical parameters of the dierent scrapes of the reeds may inuence the sonority and articulation of oboe players, however the references and demands of their musical context will direct the way that the acoustic parameters will be manipulated, inuencing the production process and adjustment of the oboe reeds.